Cultural and dietary risk factors of oral cancer and precancer - a brief overview - Zain, R.B. (Elsevier, 2001)
This is an update on cultural and dietary risk factors for oral precancer and cancer. It is an overview on ethnic differences (where possible) and socio-cultural risk factors (tobacco/areca nut/betel quid, alcohol use and dietary factors) in relation to oral precancer and cancer. While studies were from Western countries, India and China, this update also attempts to include and highlight some studies conducted in the Asia-Pacific region.